The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/acn3.734
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative vibratory sensation measurement is related to sensory cortical thickness in MS

Abstract: Objective Vibratory sensation is a quantifiable measure of physical dysfunction and is often related to spinal cord pathology; however, its association with relevant brain areas has not been fully explored. Our objective was to establish a cortical structural substrate for vibration sensation. Methods Eighty‐four individuals with multiple sclerosis (MS) (n = 54 relapsing, n = 30 progressive) and 28 controls participated in vibratory sensation threshold quantification at the great toe and a 3T MRI evaluating vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Thalamic volume was previously found to explain VDT but only in PMS patients. 34 Disappointingly, the R 2 of our statistical model was quite low. However, this aligns with those of other studies that evaluated clinical outcomes as continuous instead of dichotomous variables.…”
Section: Discussionmentioning
confidence: 78%
“…Thalamic volume was previously found to explain VDT but only in PMS patients. 34 Disappointingly, the R 2 of our statistical model was quite low. However, this aligns with those of other studies that evaluated clinical outcomes as continuous instead of dichotomous variables.…”
Section: Discussionmentioning
confidence: 78%
“…Our lab has shown that the Vibratron II is a reliable and objective way to accurately assess sensory function in MS [27]. Further, our recent findings indicate that quantitative vibratory sensation is associated with sensory cortical thickness and thalamic volume in MS [53].…”
Section: Discussionmentioning
confidence: 83%
“…Our hypothesis was con rmed SDMT was signi cantly correlated with volumes of lobule VI (p < 0.001) and crus I (p = 0.017), but not with lobule VIIB and crus II (Table 2). In addition, we correlated motor lobules with the motor measures, and found signi cant correlations between the TUG, T25FW, walk velocity, summed strength, SSST, and vibration sensation with lobules I-III, and balance to both lobules I-III and V. Measures such as the TUG and SSST require great balance demands and are complex motor tasks which require input from higher cognitive areas [56], while vibration is used as a proxy measure for proprioception [34]. Other studies have shown the lobules I-III of the cerebellum having a greater in uence on sensorimotor representations [17], whereas SSST demonstrates increased demand on coordination, balance, and ease of movement [30].…”
Section: Discussionmentioning
confidence: 99%
“…Sensation was quanti ed bilaterally at the great toe using a Vibratron II device (Physitemp, Huron, NJ, USA). The Vibratron provides reliable and objective quantitative measures of vibratory sensation in PwMS [29] and may be used as a proxy measure for proprioception [34]. Participants identi ed which of two rods was vibrating, and the threshold [35] from the worse toe was calculated and used for data analysis.…”
Section: Six Spotmentioning
confidence: 99%